Institutionalising the right to self-determination as a human right solution to problems of ethnic conflict in Africa : the case of Ethiopia and South Africa - Hansungule, Michelo (University of Pretoria, 2006)
Mini Dissertation (LLM)University of Pretoria, 2003.